Activity of Lyophilized Aqueous Extracts of Jodina rhombifolia (Hook. & Arn.) Reissek (Santalaceae) Leaves and Bark on Intestinal Transit In Mice - Tevez, Mauricio Roberto; Wendel, Graciela Haydée (Spei Domus, 2016)
Introduction: Jodina rhombifolia (Hook. & Arn.) Reissek (Santalaceae) is a part of popular therapy for treating a wide range of health problems that affect metabolism and the digestive, respiratory, musculoskeletal, cardiovascular and genitourinary systems. Our aim is to provide data that contribute to validating its use as an antidiarrheal. Materials and methods: According to the literature, we used the aqueous extract of bark, the aqueous extract of leaves and a combination of both to test the resulting effects on the intestinal activity of Rockland mice. Results: The administration of leaf and bark extracts separately did not yield significant values; however, co-administration of both extracts at doses of 125, 250 and 500 mg/kg resulted in a significant decrease—and in a dose-dependent manner—of intestinal transit in Rockland mice (p <0.05; p <0.01 and p <0.01, respectively), compared to the negative control group. Conclusions: The results obtained show us that the joint use of aqueous extract of J. Rhombifolia leaves and bark has a reducing effect on normal intestinal transit in the in vivo model and supports its use in Argentine popular medicine.